Gangguan Kepribadian Atisosial Tokoh Mike dalam Novel Endless Night Karya Agatha Christie - Alfiyani Darussalamah (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2023)
This research is entitled “Antisocial Personality Disorder of Mike in Endless Night Novel by Agatha Christie”. Endless Night novel tells the story of a man named Mike who want something in his life, but Mike has antisocial personality disorder that makes Mike do whatever he want regardless of other people. The purpose of this research is to describe the life of Mike who has an antisocial personality disorder that makes Mike have bad behaviour and harm people. The research method used in this study is qualitative method according to Bogdan and Taylor. The research approach used in this study is a literary psychology approach, this approach aims to discuss the psychology of Mike who has antisocial personality disorder. The result of this research, there are seven indications of antisocial personality disorder according to Macciardi, there are: a failure to conform to social norms; irresponsibility; deceitfulness; indifference to the welfare of others;recklessness; a failure to plan ahead; and irritability and aggressiveness. Mike has all those seven indications.